(3GSJQGJjLjGJ GdJNWjW GdGbJUGOjs - (3GHQGgje(B, (3WdYJs ((3GdbGgQI(B:s (3OGQ GdcJGH GdMOjK(B,s, 2009)
(3jVe BdjGJ GdShb hcaGAI EOGQI GdEbJUGO Gdbhej, fXQjI GdJNWjW, GdCSGdjH hGdfeGPL GdeSJNOeI aj GdJNWjW, JNWjW GdeJZjQGJ GdEbJUGOjI GdcdjI, GdJNWjW GdEbJUGOj aj LeghQjI eUQ GdYQHjI, EOGQI GdJNWjW GdEbJUGOj aj LeghQjI eUQ GdYQHjIs
(3HjHdjhZQGajG(B: (3U U(B.441-445s
Keywords: (3GdEbJUGOs; (3GdEbJUGO(B- (3Ydes; (3GdJNWjW GdEbJUGOjs